Risk factors associated with hemorrhagic cystitis after allogeneic hematopoietic stem cell transplantation. Issue 2 (April 2022) - Shen, Biao; Ma, Yueshen; Zhang, Haixiao; Wang, Mingyang; Liu, Jia; Cao, Jiaxin; Guo, Wenwen; Feng, Dan; Yang, Donglin; Zhang, Rongli; Chen, Xin; Ma, Qiaoling; et al.
Abstract : Abstract: Hemorrhagic cystitis (HC) is a common complication of allogeneic hematopoietic stem cell transplantation (HSCT). The incidence is about 7% to 68%, and some patients have to suffer a long period of frequent, urgent, and painful urination, which brings great pain. This study aimed to analyze risk factors of HC and its effect on patient survival. We collected the medical records of 859 patients who underwent HSCT at our hospital between August 2016 and August 2020. Patients with and without HC were matched using propensity score matching at a 1:1 ratio based on sex, age, and diagnosis, and logistic regression analyses were used to identify factors associated with HC. We used Kaplan–Meier curves to analyze the survival rates of patients in the HC and non-HC groups. We also analyzed the relationship between BK viral load and the occurrence of HC using receiver operating characteristic curve (ROC) analysis. After propensity score matching, there were 131 patients each in the HC and non-HC groups. In the HC group, 89 patients (67.9%) had mild HC (stage II°) and 43 (32.1%) had severe HC (stage III–IV). The median interval between stem cell transplantation and HC development was 31 (3–244) days. Univariate analysis indicated that donor age, hematopoietic stem cell source, HLA, acute graft-versus-host disease, busulfan, anti-thymocyte globulin (ATG), total body irradiation, cytomegalovirus (CMV) (urine), and BK polyomavirus (BKV) (urine) were significantly associated with HC. ATG, CMV (urine), and BKV (urine) were independent risk factors for HC based on the multivariate analysis. The Kaplan–Meier survival analysis showed no significant difference between the HC and non-HC groups ( P = .14). The 1- and 2-year survival rates in the HC group were 78.4% and 69.6%, respectively, and the corresponding rates in the non-HC group were 84.4% and 80.7%, respectively. ROC analysis indicated that a urine BKV load of 1 × 10 7 copies/mL was able to stratify the risk of HC. In conclusion, when the BKV load is >1 × 10 7, we need to be aware of the potential for the development of HC.